7095 A Comparative Analysis of the Cardiometabolic Profile of Latino Adults with 1-Hour Post-load Plasma Glucose ≥155 mg/dl, But Normal Fasting and 2-hour Glucose, Versus Those with Other Prediabetes Criteria During an Oral Glucose Tolerance Test - Torres-Aparcana, Harold L; Rosa, Agüero-Zamora; Lizarzaburu, Juan C; Villena, Lorena; Rocca, Jesus; Manrique, Katty; James, Steven (Journal of the Endocrine Society, 2024)
Abstract Disclosure: H.L. Torres-Aparcana: None. A. Rosa: None. J.C. Lizarzaburu: None. L. Villena: Employee; Self; Novo Nordisk. J. Rocca: None. K. Manrique: None. S. James: None. Background: 1-hour (h) post-load plasma glucose has been proposed as a prediabetes criterion because of its capacity to predict the development of type 2 diabetes. Objective: To compare, in a Latin population, the cardiometabolic profile of adults with 1-h post-load plasma glucose ≥ 155 mg/dl but normal fasting and 2-h glucose versus those with other prediabetes criteria during an oral glucose tolerance test (OGTT). Methods: This cross-sectional study included outpatients at a private center in Lima, Peru, between 2016-2020, aged between 20-70 years and at risk of developing type 2 diabetes. Based on OGTT results, participants were classified into five groups: [G1] all normal OGTT measurements; [G2] 1-h glucose ≥155 mg/dl but normal fasting and 2-h glucose; [G3] isolated impaired fasting glucose (IFG); [G4] isolated impaired glucose tolerance (IGT); and [G5] IFG and IGT. Indicators of hepatic insulin resistance (IR) by HOMA-IR and QUICKI, whole body IR by Matsuda Index, beta-cell function by HOMA-2B, presence of metabolic syndrome (MS), and other cardiovascular risk factors were examined by parametric and non-parametric analysis. Results: Overall, 489 people participated in the study; the mean±SD age was 44.7±7.8 years, and 251 (51.3%) were female. Of the participants, 196 (40.1%) were classified as G1, 82 (16.8%) as G2, 112 (22.9%) as G3, 37 (7.6%) as G4, and 62 (12.7%) as G5. Members of G2 (43.4±9.4 years) were younger than in G3 (47.5±8.4) and G5 (50.2±10.4), but not when compared with G4 (45.9±11.5). They also had a waist circumference (103.5±13.1 cm) greater than G1 (98.9±11.2) but similar to the prediabetes groups (G3 105.1±11.3; G4 101.9±10.9; and G5 104.1±9.9), and a HbA1c level (5.6±0.3%) that was higher than G1 (5.3±0.3), almost identical to G3 (5.6±0.3) and G4 (5.7±0.5), but lower than G5 (5.9±0.3). The G2 HOMA-IR, HOMA-2B, and QUICKI indices were like G4 but different from G3 and G5, whereas the G2 Matsuda index (2.09±1.06) differed from G1 (3.33±2.23) but was comparable to those with only one criterion of prediabetes (G3 2.30±2.17; and G4 2.44±3.25), and higher than G5 (1.79±1.72). The proportion with MS (54.3%) was higher than G1 (38.1%), close to G4 (51.1%), but less than G3 (78.6%) and G5 (85.5%). The G2 triglyceride levels were higher than G1 but were like the prediabetes groups (G3, G4, and G5). Conclusion: In this sample of Latino adults, we found that those with 1-h post-load plasma glucose ≥155 mg/dl mg/dl, but normal fasting and 2-h glucose, had similar central obesity and triglycerides compared to the other prediabetes groups. Particularly with the isolated IGT group, they shared age, hepatic IR, beta cell function, and the proportion of metabolic syndrome; the HbA1c level and whole-body IR were close to those with only one criterion of prediabetes. Finally, 1-h post-load plasma glucose ≥155 mg/dl during an OGTT may be a potential early marker to identify subjects at cardiometabolic risk. Presentation: 6/1/2024